Dialysate with different concentrations of calcium for hypocalcemia after parathyroidectomy - KONG Xing-bao; HE He; LV Qiang; WANG Shuai (Linchuang shenzangbing zazhi)
Objective To observe the efficacy of dialysate with different concentrations of calcium for hypocalcemia after parathyroidectomy in maintenance hemodialysis(MHD) patients.Methods Thirteen patients who have received parathyroidectomy from 2011 to 2014 in Hemodialysis Center were divided into group A given 1.50 mmol/L low calcium concentration dialysate,and group B given 1.75 mmol/L high calcium concentration dialysate The blood pressure,serum total calcium,blood phosphate and parathyroid hormone were determined on the operation day,and 3rd and 6th month after operation.The calcium usage was recorded.The changes of calcification scores in coronary artery were compared before and 6th month after operation color Doppler sonography and multi-slice computed tomography.Results The serum total calcium in group A and group B was significantly increased at 4 h after calcium administration as compared with that before operation(P<0.05).There was significant difference in serum total calcium and blood phosphate in both two groups before and 3 and 6 months after operation(P<0.05),but there was no significant difference in blood phosphate and iPTH between two groups before MHD(P>0.05).The serum total calcium was higher,and blood phosphate was lower in group B than in group A At 6th month after operation,the usage of calcium dose was significantly reduced,and the blood pressure was markedly elevated in group B as compared with group A(P<0.05).There were no significant changes in the calcification scores in coronary artery before and 6th month after operation(P>0.05).Conclusions High calcium concentration dialysate can correct hypocalcemia after operation and reduce the usage of calcium.But the risk of heterotopic calcification and hypertension should be noticed as well.